Second Language Acquisition and Language Education – Bridging the Interface (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Emerging in the 1970s, second language acquisition (SLA) is now a long-established field, illuminating the complexity of language learning among learners in different learning contexts, ages, and developmental stages from diverse perspectives. As an independent field within Applied Linguistics, drawing on a range of cognate fields reflecting its interdisciplinary underpinnings, the field offers a diverse range of potential insights for language practitioners. The latter include language instructors but also language education policy makers, those involved in language testing, and learners themselves. While language acquisition and language education are often confounded, the specificity of their focus is different. Notwithstanding, there is a natural interface between an acquisitional approach and an educational focus to learning a second language. That interface extends beyond instructed second language acquisition (ISLA) as a sub-field of SLA, where there is a strong focus on classroom input exposure conditions. This volume includes, but also goes beyond, ISLA to consider the interface between SLA and language education as a means of exploring a non-exhaustive range of insights that SLA can provide on the learning process of relevance to language practitioners and other stakeholders. The presentation showcases the scope for SLA and language education practitioners and stakeholders to engage in mutually beneficial dialogue.